A Study on Mechanised Log Loading in Chajpur forests of Himachal Pradesh - Mitra, S. K.; Sood, K. G. (Indian Forester, 1983)
In recent years the loadiag of timber on to trucks has become increasingly mechanised while loading by hand, a heavy, dangerous, time wasting and expensive operation hand correspondingly decreased. In this context the performance of the traxcavator, which is a caterpillar tractor fitted with wihch and loading attachment was studied in the Chajpur forests of H.P. The study reveals that the mechanise loading device performs the loading job much quicker and thereby reduces the cost of loading considerably. In view of the high risk and high energy consumption involved in manual loading this equipment has a promising future in mechanised logging operation.